Comparative transcriptomic analysis revealed important processes underlying the static magnetic field effects on Arabidopsis - Zhou, Xiujuan; Zhang, Lin; Zhang, Peng; Xu, Hang; Song, Jialei; Chang, Yafei; Cai, Tiantian; Xie, Can (Frontiers in Plant Science, 2024)
Static magnetic field (SMF) plays important roles in various biological processes of many organisms including plants, though the molecular mechanism remains largely unclear. Here in this study, we evaluated different magnetic setups to test their effects on growth and development on Arabidopsis (Arabidopsis thaliana), and discovered that plant growth was significantly enhanced by inhomogeneous SMF generated by a regular triangular prism magnet perpendicular to the direction of gravity. Comparative transcriptomic analysis revealed that auxin synthesis and signal transduction genes were upregulated by SMF exposure. SMF also facilitated plants to maintain the iron homeostasis. The expression of iron metabolism-related genes was downregulated by SMF, however, the iron content in plant tissues remains relatively unchanged. Furthermore, SMF exposure also helped the plants to reduce ROS level and synergistically maintain the oxidant balance by enhanced activity of antioxidant enzymes and accumulation of nicotinamide. Taken together, our data suggested that SMF is involved in regulating the growth and development of Arabidopsis thaliana through maintaining iron homeostasis and balancing oxidative stress, which could be beneficial for plant survival and growth. The work presented here would extend our understanding of the mechanism and the regulatory network of how magnetic field affect the plant growth, which would provide insights into the development of novel plant synthetic biology technologies to engineer stress-resistant and highyielding crops.